Politics philosophy, culture: Interviews and other writings 1977 - 1984 - Foucault, Michel 1926-1984 (New York Routledge, 1988)
Politics, Philosophy, Culture contains a rich selection of interviews and other writings by the late Michel Foucault. Drawing upon his revolutionary concept of power as well as his critique of the institutions that organize social life, Foucault discusses literature, music, and the power of art while also examining concrete issues such as the Left in contemporary France, the social security system, the penal system, homosexuality, madness, and the Iranian Revolution.